WOOD ANATOMICAL STRUCTURE AND DENSITY OF Tachigali aubl SPECIES OCCURRING IN THE SOUTHEASTERN PERUVIAN AMAZON FOREST - Portal-Cahuana, Leif Armando; Kohagura-Arrunátgu, José Andrés Hideki; Flores-Grandez, César Eduardo Martin; Frías-Quiñones, Tatiana de María de María; Tomazello-Filho, Mário (Floresta, 2023)
Tropical forests are subject to high biodiversity loss, despite their importance. However, technological studies of wood from native species are still insufficient. Knowing the technological information of the wood of more species is essential to incorporation non-traditional species into the list of commercial species and reduce the impact of these species. The techniques for collecting non-destructive wood samples from tree trunks are cheap and fast and can provide this knowledge. Here, the technological properties of the wood of three forest species of the genus Tachigali in the southeastern Amazon of Peru have been evaluated: T. alba, T. chrysaloides and T. vasquezii, using the non-destructive collection technique with a Pressler probe. Anatomical characterization and the determination of the physical properties of the woods were carried out and they were grouped according to this technical information to determine the most appropriate uses. The results show that the three species presented vasicentric paratracheal parenchyma, with basic density ranging from 0.49 to 0.77 g/cm3; finally, based on Principal Component Analysis, it allowed us to characterize two groups and determine their most appropriate use. The application of non-destructive methodologies in other species will be able to expand the technological knowledge of native species wood quickly and economically. This type of information is vitally important to support the forest management of tropical forests and increase the list of commercial species.